Psychometric properties of the Chinese version of the preoperative assessment of readiness tool among surgical patients - Bao, Guanjun; Liu, Yuanfei; Zhang, Wei; Yang, Yile; Yao, MeiQi; Zhu, Lin; Jin, Jingfen (Frontiers in Psychology, 2022)
Background: The evaluation of the surgical readiness of patients plays an important role in clinical care. Preoperative readiness assessment is needed to identify the inadequacy among surgical patients, which provides guide for interventions to improve patients' preoperative readiness. However, there is a paucity of high-level, quality tool that evaluate surgical readiness of patients in China. The purpose of this study is to translate the Preoperative Assessment of Readiness Tool (PART) into Chinese and determine the reliability and validity of the Chinese version in the population of surgical patients. Methods: Using a standard translation-backward method, the original English version of PART was translated into Chinese. A convenient sampling of 210 surgical patients was recruited from 6 hospitals in Zhejiang Province to test the psychometric properties of this scale including internal consistency, split-half reliability, content validity, structure validity and floor/ceiling effect. Results: 194 patients (92%) completed questionnaires. The Chinese version of PART achieved Cronbach’s alphas 0.948 and McDonald’s omega coefficient 0.947 respectively for the full scale. The estimated odd-even split-half reliability was 0.959. The scale-level content validity index was 0.867, and the items content validity index ranged from 0.83 to 1.0.The output of confirmatory factor analysis revealed a two-factor model (χ2 = 510.96; df = 86; p < 0.001; root mean square error approximation = 0.08) with no floor/ceiling effect. Conclusion: The Chinese version of PART demonstrated acceptable reliability and validity among surgical patients. It can be used to evaluate patients' preoperative preparation and help health professionals provide proper preoperative support.